NATURALISME SEBAGAI LANDASAN PEMBELAJARAN BERBASIS LINGKUNGAN BERBANTUAN TEKNOLOGI DALAM PEMBELAJARAN ABAD KE-21 - St. Fatima Kadir; Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The global environmental crisis and the development of digital technology in the 21st century require the world of education to integrate ecological values and technological innovation into the learning process. This study aims to analyze the relevance of naturalism philosophy as a basis for developing technology-assisted environment-based learning in the context of 21st-century learning. This research uses a qualitative descriptive approach with a library research method, with data sources in the form of books, scientific journals, and relevant academic documents. The results of the study show that the principles of naturalism, which emphasize direct experience and connection with nature, can be combined with digital technology to strengthen interactive and meaningful environmental learning. This integration can foster 21st-century skills such as critical, creative, collaborative, and communicative thinking. Thus, naturalism provides a philosophical and ecological foundation, while technology becomes a means of supporting humanistic and sustainable learning.